2017
DOI: 10.4132/jptm.2017.07.20
|View full text |Cite
|
Sign up to set email alerts
|

Placental Lesions in Meconium Aspiration Syndrome

Abstract: BackgroundMeconium aspiration syndrome (MAS) is defined by respiratory distress requiring supplemental oxygen in a meconium-stained neonate. MAS is clinically subclassified as mild, moderate, and severe according to the oxygen requirement. The aims of this study were to compare the histological findings in the placentas of MAS neonates with those of meconium-stained but non-MAS neonates and to analyze the correlation between the severity of MAS and the grade of its histological parameters.MethodsWe collected 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…Several studies have investigated antenatal and perinatal factors associated with MAS to improve the identification and management of such patients. Fetal distress or non-reassuring/abnormal cardiotocography have been frequently reported in MAS patients (43–67%) [ 18 , 19 , 20 , 21 , 22 , 23 ] as well as umbilical cord metabolic acidosis (21–24%) [ 18 , 19 , 20 ] and a low Apgar score at 5 min (18–60%) [ 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, Karabayir et al suggested that increased lactate levels in blood gases during the first hour of life may also be a risk factor for the development of MAS in MSAF patients [ 24 ].…”
Section: Factors Associated With Masmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated antenatal and perinatal factors associated with MAS to improve the identification and management of such patients. Fetal distress or non-reassuring/abnormal cardiotocography have been frequently reported in MAS patients (43–67%) [ 18 , 19 , 20 , 21 , 22 , 23 ] as well as umbilical cord metabolic acidosis (21–24%) [ 18 , 19 , 20 ] and a low Apgar score at 5 min (18–60%) [ 18 , 19 , 20 , 21 , 22 , 23 ]. In addition, Karabayir et al suggested that increased lactate levels in blood gases during the first hour of life may also be a risk factor for the development of MAS in MSAF patients [ 24 ].…”
Section: Factors Associated With Masmentioning
confidence: 99%
“…The presence of inflammation/infection in maternal history has been associated with MAS. Funisitis and/or acute chorioamnionitis have been reported in 18–65% of MAS patients [ 18 , 19 , 20 , 22 , 23 ], intrapartum fever in 49–57% [ 18 , 19 ] and a rupture of the membrane > 18 h in 5–30% [ 22 , 23 ]. Of note, Gupta et al showed an increased risk of MSAF and MAS among infants born to HIV-positive mothers although the effects of maternal HIV infection and anti-retroviral therapy remain unclear [ 25 ].…”
Section: Factors Associated With Masmentioning
confidence: 99%
“…Thureen et al (1997) showed that three of six placentas with MAS showed funisitis associated with villus ischemic changes, which may have contributed to in utero foetal hypoxia. Lee et al (2016) showed that neonates diagnosed with funisitis were at more than fourfold risks of developing MAS than those without funisitis, whereas Kim, Oh & Kim (2017) observed that the incidence and severity of funisitis were associated with those of MAS, suggesting that intraamniotic inflammation with foetal systemic inflammation might be an important upstream control variable in MAS. By performing placental histopathological examination virtually for all newborn intensive care unit (NICU) neonates, our study provided additional evidence to support the impact of intraamniotic inflammation to MAS development.…”
Section: Discussionmentioning
confidence: 99%
“…Thureen et al showed that three of six placentas with MAS showed funisitis associated with villus ischemic changes, which may have contributed to in utero foetal hypoxia (Thureen et al, 1997). Lee et al showed that neonates diagnosed with funisitis were at more than 4-fold risks of developing MAS than those without funisitis, whereas Kim et al observed that the incidence and severity of funisitis were associated with those of MAS (Lee et al, 2016;Kim et al, 2017), suggesting that intraamniotic inflammation with foetal systemic inflammation might be an important upstream control variable in MAS (Lee et al, 2016). By performing placental PeerJ reviewing PDF | (2018:12:33771:1:1:NEW 22 Mar 2019)…”
Section: Discussionmentioning
confidence: 99%